A systematic review and meta-analysis of radiation dose exposure from computed tomography examination of thorax-abdomen-pelvic regions among paediatric population - Muhammad, Nor Azura; Sabarudin, Akmal; Ismail, Nabilah; Abdul Karim, Muhammad Khalis (Elsevier, 2021)
The widespread use of computed tomography (CT) has led researchers to study CT dose exposure associated with carcinogenic effects, especially in pediatric populations. The number of pediatric patients undergoing CT scans increases every year and there is a wide range of exposure doses from the examination. In this study, we carried out systematic reviews and meta-analysis study on radiation dose received by paediatric patients during CT thorax, CT abdomen, CT abdomen-pelvis and CT thorax-abdomen-pelvis (TAP) examinations. Furthermore, the relationship between the radiation dose and the associated factors, such as scanning protocols, CT parameters, and body weight inclusive of the image quality produced was investigated. Four different databases, namely PubMed, Ovid MEDLINE, ScienceDirect, and Scopus have been used to get eligible studies published from 2010 to 2019. A total of 95 articles related to CT thorax, abdomen, and/or pelvis for paediatric patients are collected. After the final screening process, 38 articles are included in the study where 19, 8, 6 and 5 articles involving CT thorax, CT abdomen, CT abdomen-pelvis, and CT TAP examinations, respectively. Dose data, volume-weighted CT dose index (CTDIvol), dose length product (DLP), effective dose (E) and size-specific dose estimates (SSDE) are extracted in each selected studies. The highest value of mean CTDIvol, DLP, E and SSDE is found in CT abdomen-pelvis with the weight-based protocol for a patient with > 40 kg are 9.1 ± 1.2 mGy, 440.7 ± 0.0 mGy cm, 10.0 ± 0.0 mSv, and 13.7 ± 1.9 mGy respectively. We conducted a meta-analysis of selected cohort studies to explore the association between paediatric dose and region of examination which categorized based on weight. There is no difference found in CTDIvol between the group of CT thorax, CT abdomen-pelvis and CT TAP with It is established that the application of size or weight - base protocol with the adjustment of CT acquisition parameter and used of iterative reconstruction technique could substantially reduce the radiation dose while maintaining the image quality.